The Relevance of Multicultural Islamic Religious Education with the Culture of Siangga, Sikamali and Siangkaran: Ethnographic Study in Tana Toraja - Abdul Muthalib; Muhammad Tang; Abdul Azis (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This study examines the relevance of multicultural Islamic Religious Education values within the local cultures of Siangga, Sikamali, and Siangkaran in Tana Toraja. It focuses on three key questions: the conceptualization of Islamic education values in these local traditions, the process of integrating multicultural Islamic values through them, and the outcomes of this integration in social life. The research employs a descriptive qualitative method with an ethnographic approach to obtain in-depth and credible data. Data were collected through observation, structured and semi-structured interviews, and documentation, and analyzed using data condensation, data display, and conclusion drawing as proposed by Miles, Huberman, and Saldana. The findings indicate that Siangga, Sikamali, and Siangkaran serve as essential cultural foundations for building social harmony, solidarity, and moral character. Siangga promotes mutual cooperation and togetherness, Sikamali emphasizes empathy, politeness, and collective moral awareness, while Siangkaran highlights sincerity and selfless social concern. These values strongly align with Islamic principles such as ukhuwah (brotherhood), ta’awun (mutual assistance), rahmah (compassion), haya’ (moral modesty), and ikhlas (sincerity). Their integration into contextual and collaborative Islamic education reinforces tolerance, respect for diversity, and multicultural awareness.